Concept for Predictive Quality in Carbon Fibre Manufacturing - Sebastian Gellrich; Thomas Groetsch; Maxime Maghe; Claudia Creighton; Russell Varley; Anna-Sophia Wilde; Christoph Herrmann (Journal of Manufacturing and Materials Processing)
Remarkable mechanical properties make carbon fibres attractive for many industrial applications. However, up to today, carbon fibres come with a significant environmental backpack, undermining their advantages in light of a strong demand for absolute sustainability of new industrial products. Consequently, there is considerable demand for high-quality carbon fibre manufacturing, low waste production, or alternative precursor systems allowing minimization of environmental impacts. Therefore, this paper investigates the capabilities of data analytics with a special emphasis on predictive quality in order to advance the quality management of carbon fibre manufacturing. Although existing research supports the applicability of machine learning in carbon fibre production, there is a notable scarcity of case studies and a lack of a structured repetitive data analytics concept. To address this gap, the study proposes a holistic framework for predictive quality in carbon fibre manufacturing that outlines specific data analytics requirements based on the process properties of carbon fibre production. Additionally, it introduces a systematic method for processing trend data. Finally, a case study of polyacrylonitrile (PAN)-based carbon fibre manufacturing exemplifies the concept, giving indications on feature importance and sensitivity related to the expected fibre properties. Future research can build on the comprehensive overview of predictive quality potentials and its implementation concept by extending the underlying data set and investigating the transfer to alternative precursors.